Hypothermic circulatory arrest for aortic dissection with cryoglobulinemia. Issue 11 (28th July 2020) - Yamazaki, Kazuhiro; Minatoya, Kenji; Sakamoto, Kazuhisa; Kitagori, Koji; Okuda, Masanori; Murakami, Kosaku
Abstract: Cryoglobulinemia is a cold‐reactive autoimmune disease. A 64‐year‐old man with active cryoglobulinemia presented Stanford type A acute aortic dissection. He had been treated with immunosuppressive drugs and plasma exchange (PE) at our hospital; subsequently, qualitative analysis of cryoglobulin (CG) was negative. He underwent emergency ascending aorta replacement using cardiopulmonary bypass (CPB) under deep hypothermia circulatory arrest with selective cerebral perfusion. The total CPB time, aortic cross‐clamp time, and selective cerebral perfusion time were 255, 153, 56 minutes, respectively, and the minimal nasopharyngeal temperature was 17.3°C. Our patient had no significant perioperative complications. Hence, if PE is performed appropriately and CG is negative, patients with cryoglobulinemia who exhibit severe preoperative symptoms can safely undergo surgery with deep hypothermia.